The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio as a predictive indicator of CKD risk in NAFLD patients: NHANES 2017–2020 - Fan, Yong-Qiang; Wang, Hao; Wang, Pei-Pei; Shi, Zhi-Yong; Wang, Yan; Xu, Jun (Frontiers in Nutrition, 2024)
BackgroundNon-alcoholic fatty liver disease (NAFLD) and chronic kidney disease (CKD) are both closely related to dyslipidemia. However, the relationship between dyslipidemia in patients with NAFLD and CKD is not yet clear. The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is an innovative and comprehensive lipid index. The purpose of this study was to investigate the correlation between NHHR and CKD risk in NAFLD patients with or without fibrosis.MethodsThis study used data from the National Health and Nutrition Examination Survey (NHANES) from 2017 to 2020 for analysis, including a total of 4,041 subjects diagnosed with NAFLD. Among the NAFLD subjects, 3,315 individuals without liver fibrosis and 726 individuals with fibrosis. Weighted multivariate linear regression, weighted logistic regression, restricted cubic spline (RCS) curves, and subgroup analysis were used to evaluate the correlation between NHHR and CKD in patients with NAFLD.ResultsOur findings indicate that in NAFLD subjects without liver fibrosis, the highest tertile of NHHR, as compared to the lowest tertile, was inversely related to glomerular filtration rate (eGFR) (β: −2.14, 95% CI: −3.97, −0.32, p < 0.05) and positively related to CKD (OR: 1.67, 95% CI: 1.12, 2.49, p < 0.05). No significant associations were observed between NHHR and eGFR, urinary albumin to creatinine ratio (ACR) in NAFLD subjects with liver fibrosis. The RCS revealed a linear relationship between NHHR and ACR, CKD in NAFLD subjects without liver fibrosis, while a U-shaped relationship was observed between NHHR and ACR, CKD in NAFLD subjects with liver fibrosis.ConclusionIn patients with non-fibrotic NAFLD, a significantly elevated NHHR is closely associated with an increased risk of CKD and shows a linear relationship with CKD. In patients with fibrotic NAFLD, NHHR shows a U-shaped relationship with CKD. LD, Our findings underscore the practical utility of NHHR as a biomarker for early risk stratification of CKD in patients with NAFLD.